Proactive OHS Culture Program Through Competition, Motivation, and Cadre Development: A Solution for OHS Culture Building & the Shortage of OHS Personnel - Muklis, Ahmad (BKM Public Health and Community Medicine, 2024)
Purpose: This abstract aims to provide an overview of the issues related to the safety culture in Indonesia and the shortage of Occupational Health and Safety (OHS) personnel. Content: Occupational Health and Safety (OHS) is a crucial aspect of company operations, especially in sectors with a high risk of workplace accidents. Data from BPJS Ketenagakerjaan shows that the number of workplace accidents has increased over the past five years. The high rate of workplace accidents is largely due to unsafe work practices. Additionally, there is a shortage of OHS personnel in Indonesia. To create a work environment that prioritizes safety, organizations need to build and develop a safety culture in the workplace, creating an ultrasafe working environment. A program of competition, motivation, and cadre development aims to build a proactive safety culture among workers and serves as an alternative solution to the shortage of OHS personnel. The competition phase acts as an initial recruitment step for the program, while awarding and publicizing achievements serves as initial motivation. Establishing communication networks, discussions, and training sessions facilitated with OHS experts follows up of the competition phase. Regular evaluations are essential for refining and monitoring program progress (PDCA) . Competent participants will be designated as OHS agents and act as drivers of proactive safety culture in their respective units. These agents will also be responsible for overseeing work activities related to OHS. All activities within the program should provide incentives to high achievers, whether in the form of material rewards, recognition, or promotions, to maintain motivation.